2011
DOI: 10.1673/031.011.13601
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Demography of the Spider Mite,Oligonychus afrasiaticus,on four Date Palm Varieties in Southwestern Tunisia

Abstract: The date palm mite, Oligonychus afrasiaticus (McGregor) (Acari: Tetranychidae), is a serious pest of palm date fruits. Life cycle, fecundity, and longevity of this mite were studied on fruits of four date palms, Phoenix dactylifera L. (Arecales: Arecaceae)(varieties: Deglet Noor, Alig, Kentichi, and Besser), under laboratory conditions at 27 = 1 °C, 60 ± 10% RH. Total development time of immature female was shorter on Deglet Noor fruits than on the other cultivars. O. afrasiaticus on Deglet Noor had the highes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 20 publications
(28 reference statements)
0
20
1
Order By: Relevance
“…Dust particles and exuviae from different stages are trapped into these webs resulting in the dusty appearance of bunches. Under these conditions, mites grow rapidly and multiply logarithmically [5].…”
Section: Introductionmentioning
confidence: 99%
“…Dust particles and exuviae from different stages are trapped into these webs resulting in the dusty appearance of bunches. Under these conditions, mites grow rapidly and multiply logarithmically [5].…”
Section: Introductionmentioning
confidence: 99%
“…In Tunisia, four date palm varieties ('Deglet Noor', 'Alig', 'Kentichi', 'Besser') at 27°C and 60 % RH indicated that the total development time of immature females was shorter on 'Deglet Noor' fruits than on fruits of the other cultivars. The total fecundity per female is highest on 'Deglet Noor' and the lowest fecundity on 'Besser' (Ben Chaaban et al, 2011). The life cycle of O. afrasiaticus ranged from 13 days on 'Alig' date palm to '10.9' days on sorghum leaves at 27°C.…”
Section: Developmental Time and Longevity At 35°cmentioning
confidence: 99%
“…The highest rate of intrinsic increase in population (rm= 0.496) occurred at 35°C, and the doubling time of population was 1.40 at 35°C. In Tunisia, the intrinsic rates of natural increase (rm), net reproductive rates (R0) and the survival rates of immature stages of O. afrasiaticus on the host plants performs better on 'Deglet Noor' fruits while the lowest rm was on the 'Alig' variety (0.103 day) (Ben Chaaban et al, 2011).…”
Section: Life Table Parameters Of O Afrasiaticus Under Different Reamentioning
confidence: 99%
See 1 more Smart Citation
“…The old world date mite, Oligonychus afrasiaticus (McGregor 1939) (Acari: Tetranychidae) is a severe spider mite pest of date palm in arid regions and in most of North African and Middle Eastern countries (Calcat 1959;Hussain 1974;Zaher et al 1982;Palevsky et al 2003Palevsky et al , 2004Ben Chaaban et al 2011).…”
Section: Introductionmentioning
confidence: 99%